2008
DOI: 10.1002/ptr.2385
|View full text |Cite
|
Sign up to set email alerts
|

The effect of artichoke (Cynara scolymus L.) extract on ROS generation in HUVEC cells

Abstract: The effect of an artichoke extract on induced reactive oxygen species (ROS) generation in cultured human umbilical endothelial cells (HUVECs) and its reductive properties were evaluated. Preincubation of HUVEC cells with the artichoke extract at concentrations of 25-100 microg/mL for 24 h abolished ROS generation induced by LPS and oxyLDL as evaluated by the fluorescence intensity of 2',7'-dichlorofluorescein (DCF). Potent, concentration-dependent reductive properties of the artichoke extract were demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
(8 reference statements)
0
16
0
3
Order By: Relevance
“…Some researchers have isolated and identified several bioactive components of artichoke, i.e., caffeic acid, chlorogenic acid, cynarin and luteolin. These bioactive components decrease the production of reactive oxygen species (ROS), lipid peroxidation and the oxidation of low-density lipoproteins in vitro experiments (Juzyszyn et al, 2008;Zapolska-Downar et al, 2002). On the other hand, several studies have reported that vitamin C has some protective activity against Pb intoxication (Patra Shalan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have isolated and identified several bioactive components of artichoke, i.e., caffeic acid, chlorogenic acid, cynarin and luteolin. These bioactive components decrease the production of reactive oxygen species (ROS), lipid peroxidation and the oxidation of low-density lipoproteins in vitro experiments (Juzyszyn et al, 2008;Zapolska-Downar et al, 2002). On the other hand, several studies have reported that vitamin C has some protective activity against Pb intoxication (Patra Shalan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Artichoke leaf extract (ALE) is also reported to have a cholesterol-reducing effect in hypercholesterolemic subjects [21,22]. In addition, ALE has been found to decrease the production of reactive oxygen species, the oxidation of low density lipoproteins (LDL), and lipid peroxidation in in vitro experiments [23][24][25][26][27]. However, there is no study investigating the effect of ALE on serum lipid levels and tissue pro-oxidant and antioxidant status in experimental hypercholesterolemic conditions.…”
mentioning
confidence: 96%
“…These mechanisms contribute to endothelial dysfunction and may evoke endothelial cell-associated diseases. A number of studies have attempted to identify methods to protect against the inflammatory response and endothelial cell death (9)(10)(11). In the current study, the role of arazyme in the LPS-mediated inflammatory response in HUVECs was investigated.…”
Section: Introductionmentioning
confidence: 99%